2018
DOI: 10.1016/j.contraception.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Abortion in two francophone African countries: a study of whether women have begun to use misoprostol in Benin and Burkina Faso

Abstract: Objectives: This study aimed to document the means women use to obtain abortions in the capital cities of Benin and Burkina Faso, and to learn whether or not use of misoprostol has become an alternative to other methods of abortion, and the implications for future practice. Study design: We conducted in-depth, qualitative interviews between 2014 and 2015 with 34 women-21 women in Cotonou (Benin) and 13 women in Ouagadougou (Burkina Faso)about their pathways to abortion. To obtain a diverse sample in terms of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 22 publications
2
19
0
1
Order By: Relevance
“…A review of studies in Latin American found that requirements of prescriptions for medical abortion are a barrier that encourage use of informal, often more costly, sources of medical abortion [ 85 ]. In Benin, misoprostol was sought in pharmaceutical markets to avoid navigating the logistics of having to obtain a prescription [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…A review of studies in Latin American found that requirements of prescriptions for medical abortion are a barrier that encourage use of informal, often more costly, sources of medical abortion [ 85 ]. In Benin, misoprostol was sought in pharmaceutical markets to avoid navigating the logistics of having to obtain a prescription [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Benin, the abortion law allows women to access that procedure only if the life of the mother is in danger, in cases of rape, incest or malformations of the foetus [ 48 ]. Abortion in Cotonou seems to be fairly accessible in small private health centers but its cost (between 25.50 and 89.00 US dollars) [ 49 ] appears highly prohibitive for FSWs. Regardless of origin, 65% of all pregnancies occurring during sex work practice end in abortion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the context in Burkina Faso allows for some nuances, because women do not have equal access to abortion drugs, such as misoprostol. For example, a recent study in Ouagadougou has shown that the use of misoprostol is predominantly among women who have secondary and post-secondary education and who have high socioeconomic status [14]. Indeed, the introduction and use of misoprostol in Burkina Faso in the context of the restrictive abortion law gives opportunities to individuals with strong social networks and negotiating power to access misoprostol relatively easily, while those less powerful still struggle (Drabo 2019 forthcoming).…”
Section: Discussionmentioning
confidence: 99%
“…Misoprostol represents an addition to the existing abortion methods, such as vacuum aspiration, which health workers have often used to induce abortions clandestinely. Many women also use misoprostol to self-induce abortions [13,14,15,16], replacing abortifacients such as herbal tea [17], potions, high doses of anti-malarial drugs, or bleach [4]. Misoprostol does indeed diversify abortion access sources, because its marketing in pharmacies and drug stores makes it possible to access the drug in secrecy [18].…”
Section: Introductionmentioning
confidence: 99%